Crossing the phantom divide line as an effect of quantum transitions. (15th March 2021) - Dimakis, N; Paliathanasis, Andronikos
Abstract: We consider the chiral cosmological model consisting of two scalar fields minimally coupled to gravity. In the context of a Friedmann–Lemaître–Robertson–Walker (FLRW) spacetime, and for massless fields in the presence of a cosmological constant, we present the general solution of the field equations. The minisuperspace configuration that possesses maximal symmetry leads to scenarios which—depending on the admissible value of the parameters—correspond to a quintessence, quintom or phantom case. The canonical quantization of the model retrieves this distinction as different families of quantum states. The crossing of the phantom line is related to the existence of free or bound states for the Casimir operator of the symmetry algebra of the fields. The classical singularity, which is present in the quintessence solution, is also resolved at the quantum level.